Mind and the frontal lobes cognition, behavior, and brain imaging - Levine, Brian, 1963-; Craik, Fergus I. M. (New York : Oxford University Press, 2012)
The human frontal lobes are crucial to mental functioning, yet ongoing research is still uncovering their mechanisms. This text, written by leaders in frontal lobe research, provides a state-of-the-art update of patient and neuroimaging research.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Frontal lobes; Brain -- Imaging; Cognition; Neuropsychology